Baseflow Separation of the Bribin River Upstream in Gilap Cave Flowage, Sewu Mountain Karst, Gunung Kidul, Yogyakarta - Adji, T. N. (Geological Agency, 2011)
DOI: 10.17014/ijog.v6i3.124Baseflow of karst underground river is a dependable flow to recharge the underground flow within dry seasons. This research was conducted in Gilap Cave, located in the upper course of Bribin River. This location has a premeditated point for sustainable karst water along the Bribin River. The main objective of this study was to separate the components of Gilap underground river flow, with the intention on defining the proportion of baseflow component during the period of measurements. A water level data logger was installed during the period between 1 May 2006 and 31 March 2007 to determine the variation of water level during the dry season, rainy season, and when the prevalence of flood events. Subsequently, several times of discharge measurements at the time of high, medium, and low water level were carried out to define stage-discharge rating curve. Then, baseflow separation was conducted using automated baseflow separation by a digital filtering method. A digital filter value was obtained from a constant recession analysis of flood events all over the year, correlated with Maximum Baseflow Indices Value (BFImax) within karst aquifers. The result shows that during one year, 41 flood events occured in the Gilap Cave with digital filtering value of 0.996. In addition, the calculation of baseflow percentage performs that the overall value of the ratio is close to a number of around 80%. Meanwhile, the percentages within flood events vary between the range of 45-75%. From these figures, it generally confirms that flow from small fracture is still dominant to recharge dependable flow within the upper stream of Bribin River, especially in the dry season.